The Influence of The Competence And Popularity of The Preacher on The Interest of IAIN Bone Students in Participating in Preaching Activities. - Putriany, Putriany; Said, Nurhidayat Muh (Jurnal Mercusuar, 2020)
A dai plays an important role in determining the success of da’wah activities. A dai is a figure that is emulated by the mad’u (those who are invited to Islam) in all aspects of behavior and movement. In the implementation of da’wah activities, the dai and mad’u are two inseparable elements of da’wah that must exist, as they are interconnected. This study discusses the influence of dai’s competence and popularity on the interest of IAIN Bone students in participating in da’wah activities, with the aim of determining the partial and simultaneous effects of the dai’s competence (X1) and popularity (X2) variables on the interest of IAIN Bone students in participating in da’wah activities (Y). This research is a type of quantitative research (survey) with a methodological approach (positivistic-quantitative) and related to the fields of da’wah and communication. The population in this study is all IAIN Bone students, especially those in the Faculty of Da’wah and Ushuluddin, from the 2018 and 2019 academic years, totaling 293 people with a sample of 169 people using simple random sampling techniques.